Monoclonal Antibodies as Antineoplastic Therapy - Aldecoa, Franklin (2001)
Antibodies are composed of protein chains with a special Y-shaped conformation, which can be identified two identical heavy (H) chains and two identical light (L) joined by intra-and interchain disulfide bonds. Each chain has structural domains, which are globular formations resulting tertiary conformation of the protein at these levels: two light chains (CL constant, and a variable VL).